PERAN WAKAF DALAM KESEJAHTERAAN MASYARAKAT DITINJAU DARI UU CIPTA KERJA PERSPEKTIF AL-QUR’AN DAN HADITS - Yuha Komala; Marjan Mandala Putra; M. Zaidi Abdad; Nikmatullah (Universitas Muhammadiyah Bengkulu, 2025)
The government came up with the term Job Creation Law to respond to how complicated licensing regulations can make it difficult for us to move. According to the development theory, the progress of a nation is highly dependent on investment. Investment can drive economic growth to create social welfare. One of the efforts to be able to develop the community's economy is to maximize the capacity of institutions that have been regulated by Islamic teachings, such as waqf. The purpose of this study is to find out the role of waqf in community welfare reviewed from the Job Creation Law from the perspective of the Qur'an and hadith. This study uses a qualitative research method with library research. In this case, waqf has a role in the equitable distribution of welfare among the people, and poverty alleviation is one of the goals of waqf benefits. In the Qur'an and the hadith, waqf both teach to make the best possessions. Where waqf is a charitable activity that departs from obedience to Allah swt. The waqf in the Job Creation Law is not regulated directly, but is more related to the object of land acquisition. But there are arrangements related to waqf such as the management of waqf land and the utilization of waqf assets